2D Necklace Flower Constellations. (January 2018) - Arnas, David; Casanova, Daniel; Tresaco, Eva
Abstract: The 2D Necklace Flower Constellation theory is a new design framework based on the 2D Lattice Flower Constellations that allows to expand the possibilities of design while maintaining the number of satellites in the configuration. The methodology presented is a generalization of the 2D Lattice design, where the concept of necklace is introduced in the formulation. This allows to assess the problem of building a constellation in orbit, or the study of the reconfiguration possibilities in a constellation. Moreover, this work includes three counting theorems that allow to know beforehand the number of possible configurations that the theory can provide. This new formulation is especially suited for design and optimization techniques. Highlights: Necklace Flower Constellations is a new design framework to define constellations. It allows to expand the possibilities of design, maintaining the number of satellites. It contains, as a subset, Walker, Dufour, Draim and 2D Lattice Flower Constellations. The configurations obtained present stable structures with symmetric properties. The formulation is specially devised for optimization problems.